Plantas medicinais: diversidade entre comunidades rurais no Portal da Amazônia - Pereira, Arildo Gonçalo (2019)
The present work aimed to characterize and identify the medicinal plant species present in agroforestry gardens (FFA) in rural communities of family farmers in Mato Grosso, in the municipalities of Alta Floresta and Nova Canaã do Norte. The study analyzed 44 quintals of agroforestry, 24 in Alta Floresta and 20 in Nova Canaã do Norte, implanted and managed by family farmers. Guided tours were conducted in the backyards in August 2017 to map and identify the different uses of the plant resources present. A total of 151 medicinal plant species were cited and identified, divided into 62 botanical families distributed in three strata of the agroforestry consortium. We highlight the families Asteraceae (15), Lamiaceae (15), Euphorbiaceae (13), Fabaceae (10), Myrtaceae and Rutaceae. Of the total 76 species were found in both municipalities, 38 species are grown exclusively in Alta Floresta and 37 species are grown in New Canaan North. The results indicate a wide distribution of the species of medicinal plants and diversification in the backyards, in the different communities.